2018
DOI: 10.1002/asia.201801252
|View full text |Cite
|
Sign up to set email alerts
|

Lanthanide‐Catalyzed Tandem Insertion of Secondary Amines with 2‐Alkynylbenzonitriles: Synthesis of Aminoisoindoles

Abstract: A lanthanide-catalyzed intermolecular hydroamination of 2-alkynylbenzonitriles with secondary amines has been disclosed, providing a streamlined access to a range of aminoisoindoles in moderate to excellent yields. The salient features of this reaction include high bond-formation efficiency, mild reaction conditions, 100 % atomic efficiency and good functional group tolerance. This methodology has also been successfully applied to the construction of other nitrogen-containing compounds, such as 5 H-imidazo[2,1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 71 publications
0
21
0
Order By: Relevance
“…Compared to the addition reaction of organometallic reagents such as organolithium or organomagnesium to nitriles, the above-mentioned carbopalladation reagents are highly regarded due to their advantages of stability to air and moisture as well as good functional group tolerance. Inspired by hereinbefore work, as a part of our research program aimed at transition-metal-catalyzed synthesis of N-containing heterocycles with organoboron reagents and nitriles, we envisioned that palladium-catalyzed carbopalladation of 2-aminostyryl nitrile derivatives would afford 2-aminostyryl ketone derivatives easily, which might further prompt an intramolecular nucleophilic attack onto this in situ formed carbonyl group by −NH 2 with the aid of Lewis acid and/or acid medium, providing the desired 2-arylquinoline skeletons (Scheme d). Compared to direct cyclization protocol of 2-aminostyryl ketone derivatives for the construction of 2-arylquinolines, this would be an attractive synthetic strategy in research, since it provides easy and rapid access to large libraries of organic compounds with diverse substitution patterns.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the addition reaction of organometallic reagents such as organolithium or organomagnesium to nitriles, the above-mentioned carbopalladation reagents are highly regarded due to their advantages of stability to air and moisture as well as good functional group tolerance. Inspired by hereinbefore work, as a part of our research program aimed at transition-metal-catalyzed synthesis of N-containing heterocycles with organoboron reagents and nitriles, we envisioned that palladium-catalyzed carbopalladation of 2-aminostyryl nitrile derivatives would afford 2-aminostyryl ketone derivatives easily, which might further prompt an intramolecular nucleophilic attack onto this in situ formed carbonyl group by −NH 2 with the aid of Lewis acid and/or acid medium, providing the desired 2-arylquinoline skeletons (Scheme d). Compared to direct cyclization protocol of 2-aminostyryl ketone derivatives for the construction of 2-arylquinolines, this would be an attractive synthetic strategy in research, since it provides easy and rapid access to large libraries of organic compounds with diverse substitution patterns.…”
Section: Introductionmentioning
confidence: 99%
“…Pioneering work reported in 2010 by Xie and co-workers showed that titanium amides could catalyze a sequential inter- and intramolecular hydroamination of cyanoalkynes with amines or nitriles with propargylamines, affording the substituted isoindoles, isoquinolines, or imidazoles (Scheme a and b) . Similar transformations were subsequently reported using rare earth catalysts . Demir et al reported that Ph 3 PAuCl and Zn­(ClO 4 ) 2 cooperatively catalyzed tandem hydroamination/cyclization reaction of electron-deficient cyanoalkynes with amines to give 2-aminopyrroles as the main products with a different cyclization pattern (Scheme c) .…”
mentioning
confidence: 74%
“…To gain some insight into the mechanism of this rare‐earth‐metal‐catalyzed C−H bond activation/cyclization process, a set of control experiments were conducted. First, 1 H NMR monitoring revealed that the addition of Y[N(TMS) 2 ] 3 (10 mol%) to 1 a in toluene‐ d 8 at 100 °C led to the complete liberation of the (Me 3 Si) 2 N ligand (a new peak at 0.08 ppm) from the catalyst and 1 a was cleanly converted into 2 a (Figure ).…”
Section: Resultsmentioning
confidence: 99%